Innate allorecognition by monocytic cells and its role in graft rejection. Issue 2 (24th August 2017) - Lakkis, F. G.; Li, X. C.
Abstract : Innate recognition of microbial products and danger molecules by monocytes and macrophages has been well established; this is mediated primarily by pattern‐recognition receptors and is central to the activation of innate and adaptive immune cells required for productive immunity. Whether monocytes and macrophages are equipped with an allorecognition system that allows them to respond directly to allogeneic grafts is a topic of much debate. Recent studies provide compelling evidence that these cells can recognize allogeneic entities and that they mediate graft rejection via direct cytotoxicity and priming of alloreactive T cells. In addition, these studies have uncovered a mechanism of innate allorecognition based on detection of the polymorphic molecule signal regulatory protein α (SIRPα) on donor cells. Further understanding of innate allorecognition and its consequences would provide essential insight into allograft rejection and lead to better therapies for transplant patients. Abstract : This minireview introduces the novel concept of allorecognition by monocytes and macrophages, and summarizes the current understanding of its mechanisms and relevance to transplantation.